2012
DOI: 10.4014/jmb.1202.02025
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Chaperone-Like Protein CagT Plays an Essential Role in the Translocation of CagA into Host Cells

Abstract: Most of the Helicobacter pylori strains containing the cag pathogenicity island (PAI) have been associated with more severe gastric disease in infected humans. The cag PAI is composed of 27 proteins, and some of the components are required for CagA translocation into host cells as well as induction of proinflammatory cytokines, such as interleukin-8 (IL-8); however, the exact function of most of the components remains unknown or poorly characterized. In this study, we demonstrated that CagT (HP0532), which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In addition, the abundances of proteins of the T4SS (CagE and CagV) also increased in coccoid ( Supplementary Table S2 ). CagT, which is an essential structural component of the cag PAI apparatus, acts as a chaperone-like protein to promote the translocation of CagA, a bacterial oncoprotein, into host epithelial cells 45 . Consistent with our finding, antibiotic-induced coccoid forms of two clinical isolates has also been demonstrated to express higher rate of cagE mRNA than their spiral counterparts 46 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the abundances of proteins of the T4SS (CagE and CagV) also increased in coccoid ( Supplementary Table S2 ). CagT, which is an essential structural component of the cag PAI apparatus, acts as a chaperone-like protein to promote the translocation of CagA, a bacterial oncoprotein, into host epithelial cells 45 . Consistent with our finding, antibiotic-induced coccoid forms of two clinical isolates has also been demonstrated to express higher rate of cagE mRNA than their spiral counterparts 46 .…”
Section: Resultsmentioning
confidence: 99%
“…5) (104, 105). Studies have shown that surface-variable CagT is required for CagA translocation and pilus biogenesis (106, 107), and also might contribute to immune evasion by H. pylori (102). By contrast, No domains are structural modules thought to serve a variety of functions relating to transport processes.…”
Section: Modulation Of Donor-target Cell Interactions By Adapted Formmentioning
confidence: 99%
“…However, in many systems, the VirB7-like lipoproteins have acquired surface-variable regions as shown for H. pylori CagT (Terradot and Waksman 2011; Backert et al 2015), or N0 domains as shown for Xanthomonas citri VirB7 and L. pneumophila DotD (Nakano et al 2010; Souza et al 2011). Surface-variable CagT is required for CagA translocation and pilus biogenesis (Ding et al 2012; Johnson et al 2014) and might also contribute to immune evasion by H. pylori (Fischer 2011). The N0 domains of VirB7 Xac and DotD Lp are envisioned to form additional rings within or at the base of the OMC of possible importance for channel gating or communication between the IMC and the OMCC (Nakano et al 2010; Souza et al 2011) (Fig.…”
Section: Function Structure and Diversification Of T4ass And T4bsssmentioning
confidence: 99%